Association between vitamin D status and testosterone and cortisol in ice hockey players - Fitzgerald, J. S.; Orysiak, J.; Wilson, P. B.; Mazur-Rózycka, J.; Obminski, Z. (Biology of Sport, 2018)
The identification of the vitamin D receptor in tissues related to testosterone and cortisol production, in conjunction with the observed correlations between vitamin D levels and these hormones in the general population, suggest vitamin D may influence testosterone and cortisol concentrations in athletes. A crosssectional study design was used to evaluate the association between 25(OH)D and testosterone and cortisol concentrations in young male ice hockey players (n = 50). All athletes were recruited during October from the Sosnowiec area, Poland (50° N). Commercially available ELISA kits were used to determine total serum 25(OH)D, testosterone and cortisol concentrations. Serum 25(OH)D concentration was analyzed as both a continuous and dichotomous variable, binned at the criteria for deficiency (< 20 ng·ml-1), to investigate a threshold effect. Neither continuous (r = 0.18, p = 0.20) nor dichotomous (r = 0.16, p = 0.27) 25(OH)D concentration was significantly correlated with testosterone concentration. A small, inverse correlation (r = -0.30, p = 0.04) was detected between 25(OH)D and cortisol concentrations when analyzed as a dichotomous variable only. Serum 25(OH)D concentration was neither associated with testosterone (p = 0.09) nor cortisol concentrations (p = 0.11) after adjusting for age, fat free mass and fat mass in sequential linear regression. The inability of vitamin D status to independently predict testosterone and cortisol concentrations suggests that any performanceenhancing effects of vitamin D in athletes are unlikely to be mediated primarily through these hormones, at least amongst young male ice-hockey players.